2004
DOI: 10.1038/ng1384
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi sarcoma herpesvirus–induced cellular reprogramming contributes to the lymphatic endothelial gene expression in Kaposi sarcoma

Abstract: The biology of Kaposi sarcoma is poorly understood because the dominant cell type in Kaposi sarcoma lesions is not known 1-4. We show by gene expression microarrays that neoplastic cells of Kaposi sarcoma are closely related to lymphatic endothelial cells (LECs) and that Kaposi sarcoma herpesvirus (KSHV) 5,6 infects both LECs and blood vascular endothelial cells (BECs) in vitro. The gene expression microarray profiles of infected LECs and BECs show that KSHV induces transcriptional reprogramming of both cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
428
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(461 citation statements)
references
References 28 publications
27
428
0
6
Order By: Relevance
“…IGF-IR was detected by immunohistochemistry in tumor spindle cells (Catrina et al, 2005). Overexpression of the IR in KS tissue compared to normal skin was reported by Wang et al (2004) in a comprehensive microarray study, and we have independently shown that IR gene expression is induced in KSHV-infected primary DMVEC, AIDS-KS tissue and TIME cells. Furthermore, we show that the upregulated IR is phosphorylated and we observed increased activation of the downstream Erk pathway, but not the PI3K pathway, in KSHV-infected cells.…”
Section: Discussionsupporting
confidence: 58%
“…IGF-IR was detected by immunohistochemistry in tumor spindle cells (Catrina et al, 2005). Overexpression of the IR in KS tissue compared to normal skin was reported by Wang et al (2004) in a comprehensive microarray study, and we have independently shown that IR gene expression is induced in KSHV-infected primary DMVEC, AIDS-KS tissue and TIME cells. Furthermore, we show that the upregulated IR is phosphorylated and we observed increased activation of the downstream Erk pathway, but not the PI3K pathway, in KSHV-infected cells.…”
Section: Discussionsupporting
confidence: 58%
“…Recent gene expression profiling analyses have shown that spindle cells, which form the major cellular component of the lesions, most closely resemble lymphatic endothelium [19]. The lesions also contain a variable inflammatory and mononuclear cell infiltrate.…”
Section: Developing a Better Understanding Of Ks Pathogenesismentioning
confidence: 99%
“…The lesions also contain a variable inflammatory and mononuclear cell infiltrate. Studies published beginning in the late 1980s indicated that spindle cells derived from KS lesions could release, proliferate, and/or migrate in response to various growth factors that stimulate angiogenesis, including vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), interleukins -1, -6 and -8, and platelet-derived growth factor (PDGF), and over-express receptors for multiple cytokines [19][20][21][22]. Activation of these receptors stimulates multiple pro-growth and anti-apoptotic pathways via PI3kinase/Akt/mTOR and extracellular receptor kinase (ERK) [23].…”
Section: Developing a Better Understanding Of Ks Pathogenesismentioning
confidence: 99%
“…This KSHV-mediated upregulation of Prox1 leads to reprogramming of BEC to adopt LEC phenotypes by overexpressing more than 70% of lymphatic-associated genes and by downregulating many BEC-specific genes ). In contrast, expression of Prox1 is downregulated in KSHV-infected cultured LEC, which is associated with a transcriptional drift toward to BEC (Wang et al, 2004). This Prox1-mediated cell fate reprogramming in KSHV-infected cells provides an additional support to the notion that Prox1 is a master control gene specifying lymphatic endothelial cell fates Wang et al, 2004).…”
Section: Prox1mentioning
confidence: 80%